Sex And Sex-role Peculiarities Of Adolescents’ gender Images Perception In Advertisement - Brovko, Daria; Tereshtchenko, Nadia (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2016)
Gender identity formation problems are urgent nowadays in psychology. However these special traits of the process in teenagers were not enough studied. The perception of woman advertising images and inflence of these process’ on teenagers’ gender identity formation were researched. As a result it turns out that there are divergences between teenagers’ declarative attitude to gender images and their personal connotation. For girls it’s particular to have a psychosemantical approximation of both a business woman romantic girl, and a caring mother with a sexy woman. It turns out that there exist gender-role divergences of girls’ perception and connections between self-appraisal and identifiation to different gender images.